Twilight of a Golden Age : Selected Poems of Abraham Ibn Ezra - Ibn Ezra, Abraham ben Meïr, 1089-1164 (Book collections on Project MUSE., 1997)
In Victorian England, Ibn Ezra was the model for Robert Browning's "Rabbi Ben Ezra," whose philosophy reflected "robust hope and cheerfulness." Author of more than 100 books on medicine, astronomy, mathematics, philosophy, poetry, linguistics, and extensive commentaries on the Bible and the Talmud, he was the model itinerant sage - teaching and writing in his native Spain as well as in North Africa, Italy, Provence, Northern France, and England.